Data set for diet specific differential gene expression analysis in three Spodoptera moths - A. Roy (Data in Brief, 2016)
Examination of closely related species pairs is suggested for evolutionary comparisons of different degrees of polyphagy, which we did here with three taxa of lepidopteran herbivores, Spodoptera spp (S. littoralis, S. frugiperda maize (C) and rice (R) strains) for a RNAseq analysis of the midguts from the 3rd instar insect larvae for differential metabolic responses after feeding on pinto bean based artificial diet vs maize leaves. Paired-end (2×100 bp) Illumina HiSeq2500 sequencing resulted in a total of 24, 23, 24, and 21 million reads for the SF-C-Maize, SF-C-Pinto, SF-R-Maize, SF-R Pinto, and a total of 35 and 36 million reads for the SL-Maize and SL-Pinto samples, respectively. After quality control measures, a total of 62.2 million reads from SL and 71.7 million reads from SF were used for transcriptome assembly (TA). The resulting final de novo reference TA (backbone) for the SF taxa contained 37,985 contigs with a N50 contig size of 1030 bp and a maximum contig length of 17,093 bp, while for SL, 28,329 contigs were generated with a N50 contig size of 1980 bp and a maximum contig length of 18,267 bp. The data presented herein contains supporting information related to our research article Roy et al. (2016) http://dx.doi.org/10.1016/j.ibmb.2016.02.006 [1]. Keywords: Differential expression analysis (DGE), Transcriptomics, Spodoptera, Adaptation, Generalist, Specialist, RPKM (reads per kilo base of transcript per million mapped reads), RNA seq